Assessing Determinants of Lecturers’ Utilization and Attitude Towards Open Educational Resources in Universities of North-East, Nigeria - Ahmed, Bello,; C. C., Nsofor,; O. C., Falode,; Z. E. , Adamu, (Kashere Journal of Education, 2021)
The study assessed the Determinants of Lecturers’ Utilization and Attitude Towards Open Educational Resources (OER) for Knowledge Sharing in Universities of North-East Nigeria. The population of the study was 632 lecturers drawn from Federal Universities of Northeast Nigeria. The sample of the study comprised of 338 lecturers purposively selected from three Federal Universities distributed within the three states (Adamawa, Bauchi and Borno State). The study adopted concurrent embedded mixed method research design in which four Quantitative and one qualitative (QUAN + qual) research questions guided the study. The instruments used for data collection are closed ended questionnaire and focus group interview protocol. The instruments were validated by experts and subjected to reliability test using Cronbach’s alpha. Mean (x) and standard deviation (SD) was used to answer research question one to four for quantitative variables. Thematic analysis was used to answer research question five for qualitative variables using Atlas ti. Version 9.1. The findings of the study revealed that Performance expectancy, effort expectancy, social influence and facilitating conditions variables collectively influence lecturers’ use of shared OER. The study recommended among others that the University management should build on the provisions of the construct by strengthening the culture of knowledge sharing on OER repository among faculties